Análise da profilaxia pré-exposição ao HIV em serviços especializados do Ceará - França, Francisco Álisson Paula de (2021)
In 2017, the Brazilian Unified Health System (SUS) incorporated the Pre-exposure Prophylaxis to HIV (PrEP) as an additional strategy to the classic methods of prevention against infection by the Acquired Immunodeficiency Virus (HIV) already in place. PrEP consists of using a co-formulated tablet of tenofovir (TDF) and emtricitabine (FTC), capable of providing up to 96% protection against HIV. Given its recent incorporation, studies investigating its use in this setting are needed. Under this aspect, the main objective of this work was to analyze PrEP in specialized services in Ceará. This paper is a cross-sectional, analytical study, with a quantitative approach, based on secondary data obtained from the Logistic Control System of Medicines (SICLOM). Thus, the study population covered users using PrEP, registered in this system, from December 2017 to June 2020, and those with less than 180 days in using the method or who did not have the third monitoring consultation registered in SICLOM were excluded. Data collection occurred in May and June 2020. We used the Statistic Package for Social Sciences (SPSS) software for the statistical analyses and expressed the results descriptively and inferentially. Furthermore, bivariate and multivariate analyses were performed to investigate the association between the selected variables, especially the relationship between sociodemographic characteristics and risk factors for HIV infection, under full adherence to PrEP (using all doses within 90 days). At the time of data collection, 412 subjects were registered in SICLOM; however, only 231 participated in the study. Most participants were male (80.1%; n=185), gay (61.9%; n=143), with a mean age of 32±8.6 years (range 19 to 62 years old). The average time of method use was 15±5.9 months. Regarding risk factors for HIV infection, 8.7% (n=20) reported having sex in exchange for money, drugs or housing, 58.9% (n=136) reported alcohol use, 19.5% (n=45) marijuana use, and 6.1% (n=14) alcohol and marijuana use. Regarding the use of TDF/FTC, only 5.6% (n=13) had a degree of adherence lower than 80%. In this context, it was observed that characteristics of users, such as sexual practice in exchange for money, drugs, housing, and homosexuality, impacted full adherence to TDF/FTC (p= 0.033; p=0.049, respectively). In addition, another factor evidenced was the increase in the number of users who started not using condoms in any of the relationships when compared before PrEP use and after 90 and 180 days of its initiation (p<0.001). In this period, there was no statistically significant difference regarding the increase in the prevalence of sexually transmitted infections and the number of sexual partners. It was possible to observe that a significant portion of the PrEP users consumes alcohol, erection stimulants, and illicit drugs; however, this habit did not influence adherence to the TDF/FTC, which proved satisfactory (95% of the individuals had an adherence level >80%). Our findings may provide support for the comprehensive care of PrEP users since it allows us to learn about their characteristics and risk practices for HIV infection, among other determinants and associated factors.